1996
DOI: 10.1021/bi953010z
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Poly(ADP-ribose) Polymerase during Differentiation-Linked DNA Replication Reveals That It Is a Component of the Multiprotein DNA Replication Complex

Abstract: 3T3-L1 preadipocytes have been shown to exhibit a transient increase in poly(ADP-ribose) polymerase (PARP) protein and activity, as well as an association of PARP with DNA polymerase alpha, within 12-24 h of exposure to inducers of differentiation, whereas 3T3-L1 cells expressing PARP antisense RNA showed no increase in PARP and are unable to complete the round of DNA replication required for differentiation into adipocytes. The role of PARP in differentiation-linked DNA replication has now been further clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 53 publications
7
93
0
2
Order By: Relevance
“…Consistent with the¯ow cytometric data, in vivo DNA replication was maximal 20 h after release of wild-type and PARP7/7(+PARP) cells into S phase, whereas negligible [ 3 H]thymidine incorporation was apparent in PARP7/7 during the same time period (data not shown). These results are also consistent with our previous data showing that in vivo DNA replication, as assessed by incorporation of bromodeoxyuridine or [ 3 H]thymidine into newly synthesized DNA, was apparent only in 3T3-L1 control cells 24 h after induction of di erentiation-linked DNA replication, but was not detected in PARP-depleted antisense cells (Simbulan-Rosenthal et al, 1996).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the¯ow cytometric data, in vivo DNA replication was maximal 20 h after release of wild-type and PARP7/7(+PARP) cells into S phase, whereas negligible [ 3 H]thymidine incorporation was apparent in PARP7/7 during the same time period (data not shown). These results are also consistent with our previous data showing that in vivo DNA replication, as assessed by incorporation of bromodeoxyuridine or [ 3 H]thymidine into newly synthesized DNA, was apparent only in 3T3-L1 control cells 24 h after induction of di erentiation-linked DNA replication, but was not detected in PARP-depleted antisense cells (Simbulan-Rosenthal et al, 1996).…”
Section: Resultssupporting
confidence: 93%
“…We have shown that PARP-depleted 3T3-L1 cells expressing PARP antisense RNA fail to di erentiate and to undergo DNA replication that normally precedes di erentiation (Simbulan-Rosenthal et al, 1996;Smulson et al, 1995), indicating that PARP appears to be required for di erentiation-linked DNA replication in these cells. PARP is a component of a multiprotein DNA replication complex (MRC or DNA synthesome) that catalyzes replication of viral DNA in vitro and contains pol a, pol d, DNA primase, DNA helicase, DNA ligase, and topoisomerases I and II, as well as accessory proteins such as proliferating-cell nuclear antigen (PCNA), RFC, and RPA.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the absence of NAD, PARP inhibits DNA repair through binding to damaged DNA (26). Other functions proposed for PARP include roles in cellular NAD depletion (27), antirecombination and genomic stability (28), and DNA replication (29). PARP also serves as a marker for the onset of apoptosis, after which it is cleaved by proteases into DNA-binding and catalytic fragments (30).…”
mentioning
confidence: 99%
“…as discrete and separate processes. Recently, however, several were found to be members of replication complexes (uracil-N-glycosylase, 5-MeC transferase, PARP, XRCC1) [69][70][71][72]. A newer view could regard familiar processes such as NER as temporary associations made from a larger pool of DNA-interacting proteins.…”
Section: The Association Between Low-fidelity Dna Polymerases and Sismentioning
confidence: 99%